United Nations in International Politics. - Gordenker, Leon (Center for International Studies, Princeton University, 2017)
Six authors, all of whom have been associated with the Center of International Studies at Princeton University, take the occasion of the twentyfifth anniversary of the United Nations to reexamine the UN's role and work in the world today and to anticipate its future. Chapters ranging from the theoretical to the detailed and practical include "The United Nations and the International System," by Oran R. Young; "The United Nations and the League," by Stanley Michalak; "An Inquiry into the Successes and Failures of the United Nations General Assembly," by Gabriella Rosner Lande; "International Organization and Internal Conflicts," by Linda Miller; "The United Nations and Economic and Social Change," by Leon Gordenker; and "The United Nations: Various Systems of Organization," by Richard A. Falk. Originally published in 1971. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905